Heart failure in COVID‐19: the multicentre, multinational PCHF‐COVICAV registry. (17th September 2021) - Sokolski, Mateusz; Trenson, Sander; Sokolska, Justyna M.; D'Amario, Domenico; Meyer, Philippe; Poku, Nana K.; Biering‐Sørensen, Tor; Højbjerg Lassen, Mats C.; Skaarup, Kristoffer G.; Barge‐Caballero, Eduardo; Pouleur, Anne‐Catherine; Stolfo, Davide; et al.
Abstract: Aims: We assessed the outcome of hospitalized coronavirus disease 2019 (COVID‐19) patients with heart failure (HF) compared with patients with other cardiovascular disease and/or risk factors (arterial hypertension, diabetes, or dyslipidaemia). We further wanted to determine the incidence of HF events and its consequences in these patient populations. Methods and results: International retrospective Postgraduate Course in Heart Failure registry for patients hospitalized with COVID‐19 and CArdioVascular disease and/or risk factors (arterial hypertension, diabetes, or dyslipidaemia) was performed in 28 centres from 15 countries (PCHF‐COVICAV). The primary endpoint was in‐hospital mortality. Of 1974 patients hospitalized with COVID‐19, 1282 had cardiovascular disease and/or risk factors (median age: 72 [interquartile range: 62–81] years, 58% male), with HF being present in 256 [20%] patients. Overall in‐hospital mortality was 25% ( n  = 323/1282 deaths). In‐hospital mortality was higher in patients with a history of HF (36%, n  = 92) compared with non‐HF patients (23%, n  = 231, odds ratio [OR] 1.93 [95% confidence interval: 1.44–2.59], P  < 0.001). After adjusting, HF remained associated with in‐hospital mortality (OR 1.45 [95% confidence interval: 1.01–2.06], P  = 0.041). Importantly, 186 of 1282 [15%] patients had an acute HF event during hospitalization (76 [40%] with de novo HF), which was associated with higher in‐hospital mortality (89 [48%] vs. 220 [23%]) than in patients without HF event (OR 3.10 [2.24–4.29], P  < 0.001). Conclusions: Hospitalized COVID‐19 patients with HF are at increased risk for in‐hospital death. In‐hospital worsening of HF or acute HF de novo are common and associated with a further increase in in‐hospital mortality.